Working conditions and interventions of Health extension workers in the rural areas of South-Western Ethiopia - Yadeta, Gudina (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
Working conditions of health care workers considerably affect the delivery of health care services. This study examined working conditions and interventions of Health Extension Workers in the selected kebeles of Sarbo District, South-western Ethiopia. The study employed a qualitative research approach with a case study design. Being an informed by-depth interview, a researcher collected primary data from four health extension workers and a health officer of the district. The researcher analyzed and interpreted primary data thematically. Findings of the study indicated that low payment, poor transportations, unsafe working conditions, and less-supportive top management were among the restraining challenges that impede interventions and working conditions of health extension workers in the study areas. These constraining factors further lead to poor delivery of primary health care services. Therefore, this study recommends effective policy interventions to bring favorable working conditions for rural health extension workers